ANALISIS PENGGUNAAN MEDIA INTERAKTIF CANVA UNTUK PEMAHAMAN MEMBACA ANAK TUNARUNGU KELAS IV DI SLBN KABUPATEN KAMPAR - Zenita Zahro; Mufarizuddin; Rusdial Marta; Muhammad Syahrul Rizal; Joni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the use of Canva interactive media in improving reading comprehension among fourth-grade deaf students at SLBN Kabupaten Kampar. The background of this research is based on the need for learning media that can accommodate the hearing limitations of deaf students while increasing their interest and ability in reading. This research employed a descriptive qualitative method, with data collected through observation, interviews, and documentation. The research subjects included the class teacher, school principal, students, and parents. The results indicate that the use of Canva interactive media provides a significant positive impact. First, it facilitates teachers in delivering material through engaging visuals, contrasting colors, and animations that are easy for deaf students to understand. Second, students become more focused and motivated to participate in reading lessons. Third, parental involvement in supporting their children’s learning at home increases since the media can be accessed flexibly. Observations showed improvement in text comprehension and vocabulary mastery after four learning sessions. Interviews with teachers, the school principal, and parents confirmed that Canva supports learning adjustments according to the communication characteristics of deaf students. The conclusion of this study is that Canva interactive media is effective in enhancing reading comprehension among deaf students. These findings align with previous studies emphasizing the importance of visualization and interactivity in learning for students with special needs.